Legal Uncertainty and Civil Rights Vulnerability: The Consequences of Inaccurate Divorce Certificates in Indonesia’s Islamic Family Law System - Rohman, Baeti; Luthfi, A Hashfi; Adhkar, Shohibul (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2025)
This study examines how inaccuracies in divorce certificates affect a person's legal status, potentially leading to complications in civil registration, remarriage, property rights, and inheritance. The research employs an empirical juridical approach, collecting primary data through field research at the Religious Courts of Malang City and Malang Regency, as well as secondary data from legislation, court decisions, and academic literature. Interviews were conducted with judges at those two courts. The findings reveal that such errors not only undermine legal certainty but also infringe upon individuals' personal rights, as they face difficulties in proving their marital status, accessing legal protection, and exercising their civil rights. The study highlights that although legal mechanisms exist to correct documentation errors, the current procedures remain inefficient and burdensome for affected persons, necessitating a more accessible and expedited correction process. Furthermore, this research recommends the implementation of digital registration systems and stricter verification measures to minimize future errors. [Kajian ini membahas bagaimana ketidakakuratan dalam akta cerai memengaruhi status hukum seseorang, yang dapat menyebabkan komplikasi dalam pencatatan sipil, pernikahan kembali, hak atas properti, dan warisan. Metode penelitian yang digunakan dalam penelitian ini yuridis empiris dengan mengumpulkan data primer melalui penelitian lapangan di Pengadilan Agama Kota Malang dan Pengadilan Agama Kabupaten Malang, serta data sekunder dari peraturan perundang-undangan, putusan pengadilan, dan literatur akademik. Wawancara dilakukan dengan para hakim di pengadilan agama. Hasil penelitian menunjukkan bahwa kesalahan semacam ini tidak hanya melemahkan kepastian hukum tetapi juga melanggar hak-hak pribadi individu, karena mereka dapat mengalami kesulitan dalam membuktikan status perkawinan, mengakses perlindungan hukum, dan menjalankan hak sipilnya. Penelitian ini menemukan bahwa meskipun terdapat mekanisme hukum untuk memperbaiki kesalahan dalam dokumen, prosedur yang ada masih tidak efisien dan membebani individu yang terdampak, sehingga diperlukan proses koreksi yang lebih cepat dan mudah diakses. Selain itu, penelitian ini merekomendasikan penerapan sistem pencatatan digital serta verifikasi yang lebih ketat guna meminimalisir kesalahan di masa mendatang.]